Designing and piloting innovative and inclusive solutions in the agri-food systems- 3D - Nchanji, Eileen; Puskur, Ranjitha; Ketema, Dessalegn Molla; Gartaula, Hom Nath; Mukhopadhyay, Prama; Mapedza, Everisto D.; Chadha, Deepali; Lutomia, Cosmas Kweyu (CGIAR Initiative on Gender Equality, 2023)
CGIAR Gender Equality Research Initiative, HER+, explores the concept of designing and piloting innovative and inclusive solutions in agri-food systems using 3D animation. The video provides insights into the HER+ Initiative's efforts to create socio-technical innovation bundles, making a positive impact within the agricultural and food sector. Animation by Lions Cub Studio